Challenges and Opportunities Facing Public Administration in the 21st Century - Sarjito, Aris (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
In the 21st century, the field of public administration has been challenged by various political and social changes that have transformed the way governments operate around the world. The aim of this study was to examine the challenges and opportunities facing public administration in the 21st century, with a particular focus on the qualitative experiences of practitioners in the field. The research utilized a qualitative method, involving interviews with public administration professionals to gather their insights on the challenges and opportunities facing their field. Secondary data was also collected from relevant literature on the topic. The findings indicated that public administration is facing challenges such as changing public expectations, fiscal constraints, technological disruption, and political changes. On the other hand, there are also opportunities such as increased collaboration, innovation, and citizen engagement.